A three-phase solid-liquid-gas slug flow mechanistic model coupling hydrate dispersion formation with heat and mass transfer - Lange Bassani, Carlos; Barbuto, Fausto A.; Sum, Amadeu K.; Morales, Rigoberto E.M. (Chemical Engineering Science, 2018)
Pipe blockage due to gas hydrate formation is a main concern in the oil and gas industry due to the revenue losses caused by either production impairments or interruptions, and to the high costs associated to the elimination of such blockages. Assuming a hydrate formation rate in the gas-water interface based on the system subcooling, the present work models the transition from two-phase liquid-gas to three-phase solid-liquid-gas flows when hydrates form. The multiphase flow is assumed to be within the slug flow pattern region, as this is the prevailing flow regime in offshore production scenarios. The model couples mass, momentum and energy balances for the slug flow unit cell. The hydrate phase is assumed as homogeneously dispersed in the water. The gas and water consumption rates due to hydrate formation are modeled as source terms in the mass balance equations. The exothermic characteristic of the hydrate formation is taken into account in the energy conservation equation. The model provides analytic expressions for temperature and pressure distributions along the pipeline. However, the unit cell geometry is solved by numerical integration and the model closure is achieved only when empirical correlations for the slug frequency, the unit cell translational velocity and the slug aeration are used. The results from the numerical simulations are presented for the same input parameters for cases with and without hydrate formation. The discussion focuses on the influence of hydrate formation in the slug flow hydrodynamics and heat transfer. The main mechanisms affecting the mixture temperature and pressure distributions, the mixture heat transfer coefficient, the superficial velocities of the phases, the liquid loading, the slug flow frequency and the unit cell geometry are presented.
Created from Fastlane, Scopus look-up
Keywords: Flow assurance; Heat and mass transfer; Hydrates; Multiphase flow modeling; Three-phase solid-liquid-gas slug flow